THE WORLD OF VIOLENCE:A Critical Reading of the Characters in Hamid Nasser’s Novel (The Crippled Man’s Obsession) (Journal of Imam Al-Kadhim College, 2026)
This paper is an attempt to analyze the novel The Obsession of the Crippled Man  by Hamid Nasser from a psychological perspective, it seeks to understand how violence managed to leave its marks on the unconscious structure of the characters' inner feelings. The question arises of the internal Fragmentation of identities affected by Violence, causing political and social transformation, which is what Iraq experienced after 2003. This revived the collective feeling of the characters amidst their suffering from the ravages of war and oppression. They were faced with two bitter choices: either to adapt to the hostile environment or to resist and reject everything around them. Here, the research intended  to closely explore this society and its scattered identities in Hamid Nasser's novel Hāgis al-Rajul al-Kasīḥ (The Crippled Man’s Obsession)The main question here is:  How does Violence in its various forms shaped the characters’ consciousness, scattered identities & influence the narrative elements in the novel? To answer this, the study applies René Girard’s theory of mimetic desire, rivalry and fragmented identity, alongside Pierre Bourdieu’s theory of symbolic violence. The expected finding refers that, violence was dominant force permeating every detail in daily lives, transforming space and time into instruments of oppression, causing deep fractures in identity. In addition to the mechanisms of Symbolic Violence & the Normalization Of Repression as well as the psychological defense strategies employed to endure terror. Finally, It recommended to expand Academic studies on Iraqi fiction to help in deep understanding of identity fragmentation, mechanisms of symbolic violence and employ literary narrative as a tool of resistance and healing from trauma.
Keywords: Violence; Identity; Narrative; Iraqi Novel; Girard; Bourdieu